(untitled) (Research, Society and Development, 2020)
This study aimed to carry out a survey on academic publications dealing with the theme COVID-19, in order to identify which type of research - basic or applied, these publications would be aligned with. As a database, Google Scholar was chosen and the descriptor COVID-19 was used, which should be in the title or in the abstract. The search was carried out on April 3, 2020, identifying a total of 1,290,000 results, with the filter In Any Language. From this universe, the sample was delimited with the parameters of 5% error margin and 90% confidence interval, which resulted in 273 studies, ranked by relevance. The classification in basic research or applied research was based on the theoretical assumptions of Bush (1945), Orgazination for Economics Cooperation and Development (OECD, 1994), Stokes (2005) and Riazuddin (2007). The results show the prevalence of academic productions classified as basic research (68.46%) and China as the country from which the most studies on this theme were published (41.96%).